2001
DOI: 10.1046/j.1365-2796.2001.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Ehlers–Danlos syndrome type IV with a unique point mutation in COL3A1 and familial phenotype of myocardial infarction without organic coronary stenosis

Abstract: Abstract. Nishiyama Y, Nejima J, Watanabe A, Kotani E, Sakai N, Hatamochi A, Shinkai H, Kiuchi K, Tamura K, Shimada T, Takano T, Katayama Y (Nippon Medical School, Tokyo, and Chiba University School of Medicine, Chiba, Japan). Ehlers±Danlos syndrome type IV with a unique point mutation in COL3 A1 and familial phenotype of myocardial infarction without organic coronary stenosis (Case Report). J Intern Med 2001; 249: 103±108.We report on a 43-year-old male patient with Ehlers± Danlos syndrome (EDS) type IV with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…PEPIN et al [4] suggested that there was no apparent relationship between the type of complication and the location of mutations. However, it has also been suggested that the nature of the mutation can relate to phenotype [16][17][18][19][20][21][22][23]. Mutations at the very 39 end of the gene generally produce a severe form of the disease, with arterial rupture and markedly reduced life expectancy, and mutations located in the middle part or at the 59 end produce more variable phenotypes and milder variants [1,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…PEPIN et al [4] suggested that there was no apparent relationship between the type of complication and the location of mutations. However, it has also been suggested that the nature of the mutation can relate to phenotype [16][17][18][19][20][21][22][23]. Mutations at the very 39 end of the gene generally produce a severe form of the disease, with arterial rupture and markedly reduced life expectancy, and mutations located in the middle part or at the 59 end produce more variable phenotypes and milder variants [1,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The COL3A1 mutation identification method we described previously 4,5 was further modified to amplify 1 COL3A1 cDNA fragment. Total cellular RNA and genomic DNA were extracted from cultured dermal fibroblasts and complementary DNA was synthesized by priming with random hexamers as described previously.…”
Section: Mutation Identificationmentioning
confidence: 99%
“…As is often the case with catastrophic disorders, SCAR might be underreported because an acute bleeding in the pericardium is often lethal and thus likely to be recognized. In addition, pre-or postoperative CAG failed to show local coronary pathology in most cases [10].…”
Section: Discussionmentioning
confidence: 93%